The 12th International Workshops on Opportunistic Protists (IWOP-12) - Weiss, Louis M. (2013)
The 12th International Workshops on Opportunistic Protists (IWOP-12) was held in August 2012 in Tarrytown, New York. The objectives of the IWOP meetings are to: (1) serve as a forum for exchange of new information among active researchers concerning the basic biology, molecular genetics, immunology, biochemistry, pathogenesis, drug development, therapy, and epidemiology of these immunodeficiency-associated pathogenic eukaryotic microorganisms that are seen in patients with AIDS and (2) foster the entry of new and young investigators into these underserved research areas. The IWOP meeting focuses on opportunistic protists, e.g. the free-living amoebae, Pneumocystis, Cryptosporidium, Toxoplasma, the Microsporidia, and kinetoplastid flagellates. This conference represents the major conference that brings together research groups working on these opportunistic pathogens. Slow but steady progress is being achieved on understanding the biology of these pathogenic organisms, their involvement in disease causation in both immune-deficient and immune-competent hosts, and is providing critical insights into these emerging and reemerging pathogens. This IWOP meeting demonstrated the importance of newly developed genomic level information for many of these pathogens and how analysis of such large data sets is providing key insights into the basic biology of these organisms. A great concern is the loss of scientific expertise and diversity in the research community due to the ongoing decline in research funding. This loss of researchers is due to the small size of many of these research communities and a lack of appreciation by the larger scientific community concerning the state of art and challenges faced by researchers working on these organisms.